Anterior Shoulder Dislocation during Breaststroke Swimming Technique: A Case Report and Review of the Literature - Angelo V. Vasiliadis; Christos Kalitsis; George Biniaris; Antonios Saridis (Case Reports in Orthopedics)
A 36-year-old woman presented with anterior shoulder dislocation as a result of breaststroke swimming training. She complained of pain and restriction of movement. A radiograph revealed the shoulder was dislocated, and the patient was treated successfully with closed reduction. The mechanism of injury seemed to be a relation between the initial pull phase of breaststroke technique and the weakest position of the shoulder in extension and external rotation. In our experience, if a patient has a history including a shoulder dislocation, this needs to be considered carefully before incorporating aquatic therapy into the rehabilitation program. Attention must also be given to the crucial timing of initiating swimming training.